PENGARUH INSIDER OWNERSHIP, LEVERAGE, PROFITABILITY DAN FIRM SIZE TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Consumer Good yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - Ifana Qiroatul Aziza; Budi Wahono; M. Agus Salim (UNIVERSITAS ISLAM MALANG, 2017)
The purpose of this research is to examine effect of Insider Ownership, Leverage, Profitability, and Firm Size partially and together towards to the value of company. Insider Ownership, Leverage, Profitability, Firm Size as independen variabel and Company value as dependen variabel. Types of this research is explanatory research, population on this research is company Consumer Good that registered in indonesian stock exchange period 2011-2015 with purposive sampling method. The sample is nine company Consumer Good. Data analysis that used is multiple linear regression and classic assumption test. The result of research Insider Ownership have t value 0,224 (sig. 0,824 > 0,05) Leverage have t value -0,399 (sig 0,692 > 0,05) Profitability have t value 2,836 (sig. 0,007 < 0,05) next, Firm Size have t value 3,532 (sig. 0,001 < 0,05). Showed that Insider Ownership partially positiv not significant effect on the value of the company, Leverage partially negative not significant effect on the value of the company, while Profitability and Firm Size partially positive significant effect on the value of the company. And together Insider Ownership, Leverage, Profitability, and Firm Size take significant effect on company value. This is Evidence by F 7,446 (sig. 0,000 < 0,05).